Atherosclerosis in subjects newly diagnosed with human immunodeficiency virus infection. Issue 4 (18th July 2018) - Kirichenko, Tatiana V.; Myasoedova, Veronika A.; Shimonova, Tatiana E.; Melnichenko, Alexandra A.; Sviridov, Dmitri; Sobenin, Igor A.; Mazus, Alexey I.; Orekhov, Alexander N.; Bukrinsky, Michael I.
Abstract : HIV infection is associated with the increased risk of cardiovascular disease (CVD), even in patients successfully treated with the combination antiretroviral therapy (cART). However, the relationship between HIV, cART, and pathogenesis of CVD remains controversial. In the present study, we evaluated the carotid intima–media thickness (CIMT), a surrogate marker of atherosclerosis, in HIV-infected subjects receiving or not receiving cART. One hundred nine newly diagnosed HIV-infected subjects and one hundred nine uninfected age-matched controls (all males) without the history of CVD, hypertension, or diabetes were recruited into the present study. Cross-sectional analysis at baseline (BL) showed significantly increased levels of triglycerides (TG) and decreased levels of high-density lipoprotein (HDL) in HIV-infected subjects, indicating that these risk factors for CVD appeared during the undiagnosed period of HIV infection. Nevertheless, no differences in CIMT were detected between the groups, suggesting that these risk factors were yet to be translated into the clinical disease. The prospective arm of the study, which included 37 HIV-infected and 23 uninfected subjects, showed higher CIMT increase in HIV-infected group than in control group ( P =0.0063). This difference was significant for both cART-treated ( P =0.0066) and untreated ( P =0.0246) subgroups relative to the uninfected subjects, but no difference was found between the HIV-infected subgroups. These results suggest that cART does not reverse the HIV-induced increase of CIMT. The present study demonstrates that the progression of atherosclerosis is accelerated in HIV-infected subjects regardless of treatment.